A pH-sensitive methenamine mandelate-loaded nanoparticle induces DNA damage and apoptosis of cancer cells. (15th October 2017) - Zhang, Linhua; Hao, Wenbo; Xu, Lv; Gao, Yongfeng; Wang, Xusheng; Zhu, Dunwan; Chen, Zhuo; Zhang, Xudong; Chen, Hongbo; Mei, Lin
Graphical abstract: Abstract: Methenamine mandelate is a urinary antibacterial agent, which can be converted to formaldehyde in urine that has a relatively low pH of average 5.5–6.8. Here, we prepare a pH-sensitive PLGA-based nanoparticle containing both methenamine mandelate and NaHCO3 . Methenamine mandelate/NaHCO3 -coloaded nanoparticle could enter cells via endosome/lysosome pathway. The pH in lysosomes and endo-lysosomes is approximately 5.0. In the acidic environment, NaHCO3 reacts with proton and produce CO2 bubbles, which burst nanoparticles and lead to the rapidly release of methenamine mandelate. Meanwhile, methenamine mandelate was then quickly converted to a sufficient amount of formaldehyde in this acidic environment, which induced DNA damage and DNA damage response (DDR). Consequently, methenamine mandelate/NaHCO3 -coloaded nanoparticles caused cell cycle arrest, cell growth inhibition and apoptosis of cancer cells. Moreover, methenamine mandelate/NaHCO3 -coloaded nanoparticles also show intensive inhibitory effect on the growth of MCF-7 xenograft tumor in vivo . Therefore, methenamine mandelate/NaHCO3 -coloaded nanoparticle is a promising type of formulation for the treatment of cancer, which could give the "old drug" methenamine mandelate a new anti-cancer function in clinical. Statement of Significance: Methenamine mandelate is a urinary antibacterial agent, which can be converted to formaldehyde in urine that has a relatively low pH of average 5.5–6.8. Here, we prepare a pH-sensitive PLGA-based nanoparticle containing both methenamine mandelate and NaHCO3 . Methenamine mandelate/NaHCO3 -coloaded nanoparticle could enter cells via endosome/lysosome pathway. The pH in lysosomes and endo-lysosomes is approximately 5.0. In the acidic environment, NaHCO3 reacts with proton and produce CO2 bubbles, which burst nanoparticles and lead to the rapidly release of methenamine mandelate. Meanwhile, methenamine mandelate was then quickly converted to a sufficient amount of formaldehyde in this acidic environment, which induced DNA damage and DNA damage response (DDR). Methenamine mandelate/NaHCO3 -coloaded nanoparticle is a promising type formulation for the treatment of cancer, which could give the "old drug" methenamine mandelate a new anti-cancer function in clinical.